Potential Role of Microplastics and Nanoplastics in the Pathogenesis of Endometriosis: An Environmental Health Narrative Review - Radziwon, Maja; Borowski, Konrad; Pastuszek, Oskar; Bolesta-Okuniewska, Emilia; Michalak, Pawel; Marchwińska-Pancer, Aleksandra; Kopeć, Katarzyna; Ceryn, Julia; Wicher, Anna Maria (Journal of Education, Health and Sport, 2026)
Microplastics and nanoplastics (MNPs) have emerged as ubiquitous environmental contaminants that are increasingly detected in human biological matrices, including blood, urine, placenta, and reproductive tissues [1–3]. Due to their small size, persistence, and physicochemical properties, these particles are capable of entering the human body through ingestion and inhalation, followed by systemic distribution [4]. Endometriosis is a chronic, estrogen-dependent inflammatory disease affecting approximately 10% of women of reproductive age and is characterized by immune dysregulation, oxidative stress, mitochondrial dysfunction, and altered hormonal signaling [5–7]. Growing evidence indicates that exposure to environmental pollutants may modulate molecular pathways relevant to the development and progression of endometriosis [8]. Experimental studies demonstrate that MNPs can induce oxidative stress, activate inflammatory signaling cascades, disrupt endocrine function, and alter immune cell behavior—mechanisms that overlap with the established pathophysiology of endometriosis [9–12]. Recent reports describing the presence of microplastics in human endometrial tissue further raise concerns regarding direct tissue-level exposure [13]. This narrative review summarizes current PubMed-indexed evidence on human exposure to microplastics and nanoplastics, their biological effects relevant to female reproductive health, and the mechanistic plausibility of their involvement in endometriosis pathogenesis, while highlighting existing knowledge gaps and methodological limitations.